Administrative Dysfunction in Non-Quota Hajj Management: An Analysis of the 2025 Furoda Hajj Case in Indonesia - Nunung, Ai; Latifah, Latifah; Fatmawati, Fatmawati (Department of Public Administration, 2025)
This study discusses the failure of public services in the implementation of non-quota Hajj (Furoda Hajj) in 2025 in Indonesia using an administrative analysis approach. The case of Haji Furoda 2025 reflects the dysfunction of the service, ranging from weak verification, lack of supervision by PIHK, to unclear rules in handling violations. This research uses a qualitative descriptive approach to provide an in-depth overview of the studied phenomenon. The Data Collection Technique through In-Depth Interviews was carried out in a semi-structured manner, including the affected Furoda Hajj pilgrims, PIHK Leaders, DPD Chairmen, and literature in the public policy and state administration. Data Analysis Technique: The data obtained is analyzed using the Miles and Huberman model interactive analysis technique. The results of the study show that the failure in the case of Haji Furoda stemmed from the failure of public services not only due to technical errors, but also due to institutions that were unable to manage, coordinate, and adapt. The implementation of non-quota hajj faces various administrative problems that are not accountable and unresponsive. Institutional failure can be seen in the inability to ensure accountability and successful outcomes. The data discrepancy between PIHK and the Hajj authorities shows weak public information management. In addition, poor inter-agency coordination and low administrative resilience make the bureaucracy fail to anticipate emergencies. Regulatory ambiguity and weak law enforcement further worsen the situation, opening up space for abuse of authority. This study recommends the need for governance reform of the implementation of non-quota hajj through clearer regulations, strict audit mechanisms, cross-agency data integration, empowerment of frontline workers, and service design oriented to the needs of pilgrims. This effort is important so that non-quota hajj services in the future are more transparent, accountable, and able to provide stronger protection for pilgrims.